Study on the potential of repair fire-damaged reinforced concrete beams using ultra high performance concrete with curing at ambient temperature - Muhd Afiq Hizami Abdullah (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objectives of this study includes the production of UHPC as repair material and its effect on repaired fire-damaged concrete beam.